TINJAUAN METODE POTENSIAL SINTESIS BIONANOKOMPOSIT ANTISTATIS YANG DIPERKUAT DENGAN MONO-DIASILGLISEROL DAN NANOKRISTAL SELULOSA - Muhammad Syukur Sarfat; Dwi Setyaningsih; Farah Fahma; Nastiti Siswi Indrasti; Sudirman Sudirman (Department of Agroindustrial Technology, Bogor Agricultural University, 2022)
In the last 10 years, the research about the technology of bionanocomposite synthesis has increased rapidly,starting from the simple technology to advanced technology of synthesis. From the several technologies ofsynthesis of bionanocomposite that have been developed, each has its own advantages and disadvantages.Therefore, the selection of the right technology of synthesis of bionanocomposite is one of the indicators of successin its synthesis. This review identified the latest developments in technology of synthesis of bionanocomposite andfocuses on methods of synthesis of bionanocomposite was most widely used and a technology that has advantagesover other technologies. It is hoped that this review can provide information about methods of synthesis ofbionanocomposite in general and specifically can provide information about methods of synthesis ofbionanocomposite reinforced with mono-diacylglycerol (M-DAG) and cellulose nanocrystal (CNC). Based on theidentification from several result of research, potential method to synthesis of bionanocomposite are combinationof two methods, namely twin-screw extrusion method and injection molding method. Those technologies can be analternative potential methods of synthesis of antistatic bionanocomposite reinforced with M-DAG and CNC.Keywords: cellulose nanocrystal, injection molding, mono-diacylglycerol, technology of synthesis of antistaticbionanocomposite, twin-screw extrusion